Decoloniality and the Heritage-Based Education 5.0 Curriculum in Zimbabwe - Wuta, Rodwell Kumbirai (Cultural Conflict and Integration, 2026)
Zimbabwe has a chequered history of settler colonialism whose long-lasting effects and structures are configured into a matrix called ’coloniality’ (the colonial logic). In the first three decades of independence, Zimbabwe’s higher and tertiary education curriculum was in an inherited situation as it followed the colonial Education 3.0 Model. Hence, it remained an education for disenfranchisement and disempowerment. In 2019, the Zimbabwe Government sought to address this anomaly by operationalising the Heritage-Based Education 5.0 curriculum (HBE 5.0 curriculum). With decolonial lenses, therefore, this review paper examines Zimbabwe’s HBE 5.0 curriculum in terms of the potential to counteract and challenge the vestiges and legacies of colonialism that continue to afflict Afro-Zimbabweans in the postcolonial era. Informed by the postcolonial and Afrocentric theories, the paper discourses the decolonial outlook of the HBE 5.0 curriculum, estimating the emancipatory and anti-imperialistic predispositions that render it fashionable within the postcolonial dispensation. As emerging from the discussion, the HBE 5.0 curriculum is to a larger extent replete with decolonial proclivities consistent with critical consciousness and Sankofa. Hence, the said curriculum is strategically positioned to contribute to the rediscovery, restoration, and reparation of Afro-Zimbabwean power, knowledge, and being. With its penchant for decoloniality, therefore, the HBE 5.0 curriculum is envisioned to contribute significantly to the moulding of a new humanity living in a free, united, peaceful, and prosperous Zimbabwe. Consequently, the paper recommends escalation of critical consciousness, Sankofa, and the heritage-based philosophy to underpin the Education 5.0 curriculum within the decolonial trajectory of unlearning Western ideologies.